The role of polyamines in plants: A review - Aya Ihsan Rashan; Rana T. Altaee; Farah Sameer Salh; Omar Younis AL-Abbasy; Al-Lehebe, Nashwan (Plant Science Today, 2023)
Polyamines (PAs) are linear alkali nitrogenous with two, three or more amino groups that have a low molecular weight. PAs are created by organisms thru metabolism and can be found in nearly wholly cells. They are considered a unique type of plant stimulant because they acts significant roles in many kinds of plant growth and developmental stages as well as stress responses. More evidence suggests that the PA can be produced endogenously or exogenously applied to improve plant reproduction, productivity, and bear stress. While the mechanism of polyamines influencing plant growth and stress responses is still not clear. We are making an attempt to supply an inclusive review of the available literature that explained the association between PAs and flowering, stress responses and senescence. This review aimed at this is focused and abbreviates how PAs enhances and increase plant productivity and then serve as a foundation for forthcoming study on the mechanisms of PAs exploit in plant reproduction and growth.